Thermohydraulic performance evaluation of a heat exchanger mounted with oval inclined twisted rings - P. Samruaisin; V. Chuwattanakul; Piphatpong Thapmanee; Manoj Kumar; Paisarn Naphon; Naoki Maruyama; M. Hirota; Smith Eiamsa–ard (Engineering Science and Technology an International Journal, 2025)
This research examines the effects of oval inclined twisted rings (I-TRs) on thermal performance characteristics. Heat transfer enhancement, friction factor, and thermal enhancement factor tests were conducted under uniform wall heat flux with Reynolds numbers ( Re ) varying from 6000 to 20,000. A systematic investigation was carried out to examine the influence of different pitch ratios ( p/D ) and oval-ring inclination angles ( θ ) on thermal enhancement factor ( TEF ). The experimental results reveal that the Nusselt number increases with decreasing pitch ratio ( p/D ) and inclination angle ( θ ) of the I-TRs. At p/D = 1.5, the Nusselt numbers are approximately 8.59 % to 18.78 % higher than those for I-TRs with p/D values of 2.0 and 2.5. At the smallest inclination angle, θ = 30°, the Nusselt numbers are approximately higher than those at θ = 45°, 60°, 75°, and 90° by around 1.56 %, 7.21 %, 13.74 %, and 27.14 %, respectively. At a p/D ratio of 1.5 and an inclination angle of θ = 30°, the resulting thermal enhancement factor ( TEF ) consistently exceeds unity across the entire Reynolds number (Re) range. In contrast, for other geometries and configurations, some TEF values fall below unity at higher Re . Within the studied range, the highest TEF of 1.12 is achieved at θ = 30°, p/D = 1.5, and Re = 6,000. The key finding suggests that the performance of the thermal system is highly dependent on both the configuration and operational conditions.
Keywords: Heat Transfer and Optimization; Heat Transfer Mechanisms; Heat Transfer and Boiling Studies